2017
DOI: 10.1017/s1041610216002374
|View full text |Cite
|
Sign up to set email alerts
|

Through the eyes of others – the social experiences of people with dementia: a systematic literature review and synthesis

Abstract: Experiences such as loss and diminishing identity have previously been understood as a direct result of dementia, with little consideration of interpersonal influences. This review notes that people with dementia actively engage with others, whose responses can foster or undermine social well-being. This dynamic relational aspect may contribute to emerging understandings of social health in dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…The social experiences of people with dementia and the dynamics within social networks are now being described (Vernooij-Dassen, Moniz-Cook, & Jeon, 2018). For example, an investigation of lived experiences revealed that people with dementia can feel they are being treated as an 'other' rather than 'one of us', and as 'lesser' rather than a full, valued member of society (Patterson, Clarke, Wolverson, & Moniz-Cook, 2018). Fear of being unable to communicate according to accepted norms and the shame of revealing deterioration has been shown to prevent people with dementia from engaging in social contacts (Donkers et al, 2018).…”
Section: Social Healthmentioning
confidence: 99%
“…The social experiences of people with dementia and the dynamics within social networks are now being described (Vernooij-Dassen, Moniz-Cook, & Jeon, 2018). For example, an investigation of lived experiences revealed that people with dementia can feel they are being treated as an 'other' rather than 'one of us', and as 'lesser' rather than a full, valued member of society (Patterson, Clarke, Wolverson, & Moniz-Cook, 2018). Fear of being unable to communicate according to accepted norms and the shame of revealing deterioration has been shown to prevent people with dementia from engaging in social contacts (Donkers et al, 2018).…”
Section: Social Healthmentioning
confidence: 99%
“…However, each person's resilience narrative also focussed on using personal strengths and resources as they made their own 'journey' through dementia. Humour and gratitude appeared to be key aspects of this, reflecting their preservation and functions in living with dementia (see Hickman, Clarke & Wolverson, 2018;Pearson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An absence of care preferences could reflect a low level of concern regarding acquiring dementia; healthy people are more likely to worry about a family member developing dementia than about themselves developing dementia . Thus, their attitudes toward dementia mean that they consider people living with dementia as “others” rather than “one of us,” and this results in a social exclusion of people with dementia . Factors that can contribute to such apathy regarding care preferences should be further examined in order to increase the general public's awareness of the risks and consequences of dementia, as well as the availability of related coping resources.…”
Section: Discussionmentioning
confidence: 99%